Peningkatan Kemampuan Hafalan Materi Al-Quran Hadis melalui Metode Index Card Match pada Siswa Kelas VIII-F MTs Negeri I Bantul - Mafrudah Mafrudah (Jurnal Pendidikan Madrasah, 2018)
This study is purposed to find out how to improve students' motivation and learning outcomes through Index Card Match method in memorize Al Qur’an Hadis. The research was designed as a classroom action research. This reseach using classroom action reseach by employing two cicles, comprising the planning, actuating, observation, and reflection. The subject of this research was VIIIF grade students of MTs Negeri 1 Bantul of academic year 2016-2017. The results of this study indicate a significant increase in learning motivation. The percentage of students' learning motivation in the meeting I of cycle I, the student motivation was 78% and went up to 88,46% at meeting II of cycle II. There were 66,66% of total studens score above the Minimum Passing Grade (KKM) at Pre-cycle. At the meeting of cycle I and II, students who score above the KKM rose to 92,30%. In short, the implementation of Index Card Match methode in memorize Al Qur’an Hadis course can improve motivation and learning outcomes by modifying certain substances that are the use of attractive media, seating arrangements, and effective classroom management strategies.